Diretrizes para elaboração de uma política para o serviço de referência: uma proposta para bibliotecas universitárias - Soares, Priscila Gonçalves (2022)
The general objective of this study is to identify, on specific bases in the area of Librarianship, which are the guidelines that should guide the construction of a policy to be applied in the reference service of university libraries. As specific objectives, it is planned to map, in the specialized literature, the principles related to the provision of services for the provision of services; understand the context of the reference service within librarianship and encourage discussions of the results found. It justifies itself to be an element for the services of thematic reference aggregated with the university and proposes to be more public a contribution to the professional scientific field and to the community - it is one that interests the area, as from one that interests the area practical object and practical object, as it assists in the professional development of reference librarians in university libraries and for the service itself The research begins by understanding what place the reference service occupies within the area of services and which are its specificities and peculiarities. From then on, it is necessary to understand it in its history and evolution in the librarianship area, what role this service occupies within the university library, who is the reference librarian and who are the users. In addition to this reflection, it is also important to understand the reason for proposing guidelines for a policy in the reference service. In the methodological course section, a characterization research that is descriptive and exploratory at the same time is presented. Regarding the approach, it presents itself as qualitative. As for the end, it is characterized as an applied research that aims to produce knowledge that can be applied in practice. Regarding the medium, a bibliographic research will be carried out. The method used is used in content analysis, being applied and studied in 27 articles (technical-scientific and, the pathetically analyzed, were identified from the thematic pre-analyses17 (sixteen) codes. In the results and discussions section, the excerpts were identified mentioned and each code identified in the articles about each identified topic was identified. In conclusion, the central areas of the text are highlighted and a reflection of what the reference service is for this author.